Union of the Comoros : Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Union of the Comoros. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Union of the Comoros' Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument. The Comoros' authorities should use fiscal policy to cushion the adverse effects of the coronavirus disease 2019 shock and bring the fiscal position back in line with medium-term paths once the crisis has passed. In addition to expanding very substantially healthcare spending to meet the population's pandemic-related needs, the authorities should consider giving targeted and temporary support to the most vulnerable. Monetary policy should focus on maintaining the exchange rate peg. At the same time, the authorities should use all tools at their disposal to safeguard the stability of the banking system, including by providing liquidity to banks facing liquidity pressures and addressing loan servicing difficulties. Beyond implementing their pandemic preparedness plan and strengthening the health care system's ability to respond to pandemic needs, the authorities are considering delaying deadlines for tax filings and temporarily lowering customs duties for certain imports. They will monitor inflation developments and maintain the exchange rate peg to the euro. The authorities will also do all they can to ease liquidity strains in the banking system. They are also are working with banks to enable targeted loan maturity extensions.